Discover and Unfold the Mystery of Chinese Medicine - Sng Kim Sia; Lin Xun (Wolters Kluwer Health/LWW, 2019)
This article shares my experience and journey in Chinese Medicine where I started back in 2014 in Malaysia for my bachelor's degree, and subsequently led me in continuing my postgraduate studies in Shanghai University of Traditional Chinese Medicine.